2020
DOI: 10.1038/s41377-020-0311-2
|View full text |Cite
|
Sign up to set email alerts
|

High-speed femtosecond laser plasmonic lithography and reduction of graphene oxide for anisotropic photoresponse

Abstract: Micro/nanoprocessing of graphene surfaces has attracted significant interest for both science and applications due to its effective modulation of material properties, which, however, is usually restricted by the disadvantages of the current fabrication methods. Here, by exploiting cylindrical focusing of a femtosecond laser on graphene oxide (GO) films, we successfully produce uniform subwavelength grating structures at high speed along with a simultaneous in situ photoreduction process. Strikingly, the well-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(101 citation statements)
references
References 51 publications
1
100
0
Order By: Relevance
“…Hence, several groups are exploring the (contactless) formation of LIPSS on various overlayer materials [ 86 , 87 ]. Furthermore, following the general trend of research on graphene (triggered by the Nobel prize awarded in 2010), several authors studied the formation of LIPSS on graphene or graphene oxide-covered substrates [ 88 , 89 , 90 , 91 , 92 ]. It was demonstrated that LIPSS manifesting via structural modifications of the graphene or the material underneath can be used as local probe of plasmonic resonances [ 91 , 92 ].…”
Section: Recent (Ongoing) Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, several groups are exploring the (contactless) formation of LIPSS on various overlayer materials [ 86 , 87 ]. Furthermore, following the general trend of research on graphene (triggered by the Nobel prize awarded in 2010), several authors studied the formation of LIPSS on graphene or graphene oxide-covered substrates [ 88 , 89 , 90 , 91 , 92 ]. It was demonstrated that LIPSS manifesting via structural modifications of the graphene or the material underneath can be used as local probe of plasmonic resonances [ 91 , 92 ].…”
Section: Recent (Ongoing) Trendsmentioning
confidence: 99%
“…Furthermore, following the general trend of research on graphene (triggered by the Nobel prize awarded in 2010), several authors studied the formation of LIPSS on graphene or graphene oxide-covered substrates [ 88 , 89 , 90 , 91 , 92 ]. It was demonstrated that LIPSS manifesting via structural modifications of the graphene or the material underneath can be used as local probe of plasmonic resonances [ 91 , 92 ]. LIPSS for sensing applications: One of the first applications of LIPSS came up in the context of black silicon that can be generated upon ultrashort laser processing of silicon as hierarchical surface morphology consisting of micrometric Spikes [ 93 ] covered with nanometric LIPSS.…”
Section: Recent (Ongoing) Trendsmentioning
confidence: 99%
“…Furthermore, the extraordinary optical properties of metasurfaces enable the perfect absorption of light [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ], and light manipulating applications such as beam splitting [ 31 , 32 , 33 ], verification and enhancement of the spin Hall effect [ 34 , 35 , 36 ], asymmetric transmission [ 37 ], multifunctional waveguides [ 38 ], and other light-manipulation applications [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. In addition, the researches on various materials of the metasurfaces have been actively reported: a metasurface-based solar reflector using vanadium dioxide (VO 2 ) [ 43 , 50 , 51 , 52 , 53 ], a study on the manufacturing of graphene oxide film for anisotropic photoresponse [ 54 ], and the scalable nanostructures of molybdenum disulfide (MoS 2 ) [ 55 ]. However, in order for existing bulk optical devices or components to be completely replaced with metasurfaces, those metasurfaces must be fabricated consistently with a large area and high throughput.…”
Section: Introductionmentioning
confidence: 99%
“…Transactions of the ASME plasmonic lithography (FPL) was presented as large-area manufacturing technique to generate nanoscale patterned photoreduction of graphene oxide (GO) films on a silicon substrate [440]. Periodic grating structure (∼680 nm period) can be induced at a centimeter scale.…”
Section: Laser Direct Processing Of Nanomaterials and Their Heterostrmentioning
confidence: 99%